Macro Development and Micro Social Processes: Development as Discourse in Nepal - Ghimire, Sujan (Occasional Papers in Sociology and Anthropology, 2010)
This paper points out that to understand development processes, examining aid impacts at local level is as important as studying the impacts of development at the macro level. Studying development at local levels entails understanding the different societal processes triggered off by aid including the undesired and unplanned consequences. DOI: 10.3126/opsa.v11i0.3038 Occasional Papers in Sociology and Anthropology Vol.11 2009 221-243